THE DETECTION OF NEWCASTLE DISEASE TITER ANTIBODIES ON BROILERS THAT GET VACCINATED ON THEIR ONE-DAY-OLD HATCHERY - Arnaya, Ketut Ari Andhita Badraresta; Suardana, Ida Bagus Bagus Kade; Nindhia, Tjokorda Sari (Buletin Veteriner Udayana, 2023)
Vaccination when the maternal antibody is high may cause neutralization of the antibody thus the immunity response is not most optimal.  The measurement of titer antibodies after vaccination is an indicator to define success of the vaccination and it can be tested using the Hemagglutination Inhibition serology. This research aims to acknowledge until what age the titer antibodies shown seropositive on broilers which are vaccinated on the one-day-old hatchery.  The data was obtained by random sampling from the broilers population which are taken 4 times on the day 7, day 14, day 21 and day 28.  The data then is being analyzed using analysis method of variance, which is continued with regression analysis.  The research result shows that broilers which have been vaccinated on the one-day-old hatchery only produce seropositive titer until 13 days old with 4.2 HI log 2 titer and began to decrease at 14 days of age with 3.9 HI log 2 titer. The conclusion of this study is that broilers vaccinated on one-day-old hatchery produced seropositive titers up to 13 days of age. Suggestions need to be given a booster vaccination at the age of 13 days in broilers vaccinated on the one-day-old hatchery.